Penerapan Pelajaran Kooperatif Tipe Snowball Throwing Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPS Siswa Kelas IV Semester II SD Negeri 4 Pertima - Ni Made Juliani (Jayapangus Press, 2019)
This study aims to improve student learning activities and outcomes on social studies subjects through the implementation of the snowball throwing type cooperative learning model. The research was conducted in two cycles, with the research subjects namely fourth grade students of Semester II SD Negeri 4 Pertima in the Third Year with a total of 31 students. This type of research is Classroom Action Research using observation methods to measure student learning activities and test methods to measure student learning outcomes. After the data is collected, then it is analyzed using descriptive statistical methods. The results obtained from this study are, in the first cycle the percentage of student learning activities reaches 66.8% and in the second cycle the percentage of student learning activities increases to 81%. Thus student learning activities have increased by 14.2%. In addition to student learning activities, student learning outcomes also increased, in the first cycle the percentage of student learning outcomes reached 66.1% with learning completeness of 67.74%. In the second cycle the percentage of student learning outcomes increased to 70.16% with learning completeness that had reached 100%. Thus student social studies learning outcomes increased by 3.55% and student learning completeness increased by 32.26%. For this reason the Cooperative Learning Throwing Type model if applied in Social Studies Lessons in Grade II of semester II in SD Negeri 4 Pertima is very effective, so that education services become more qualified and recognized by the community supporting education in SD Negeri 4 Pertima Karangasem District, Karangasem Regency.